The National Human Rights Plan 2018-2021: Balance sheet of the preparation process - Rodríguez Gómez, Edgardo (2020)
The article offers an overview of the process of elaboration of the Peruvian National Human Rights Plan 2018-2021, as well as the innovations that this Plan offers when compared to its predecessor. On the other hand, the paper analyzes the conceptual and methodological pillars on which the Plan is built, assesses the guidelines from which the strategic actions directed towards groups of special protection are derived.